VECTOR APPROACH TO A NEW GENERALIZATION OF FIBONACCI POLYNOMIAL - Ashok Dnyandeo Godase; Machindra Baban Dhakne (Journal of New Theory)
Abstaract−In this paper we introduce a new generalization of Fibonacci polynomial and vectors of length d are defined for these Polynomials. Using these vectors some properties for Generalized Fibonacci Polynomial (GFP) are established